Adolescent weight management counseling: The effectiveness of an online training program for primary healthcare professionals in Indonesia. - Fransisca H Agung; Rini Sekartini; Nani Sudarsono; Aryono Hendarto; Retno Asti Werdhani; Meita Dhamayanti; Retno Pudjiati; Lathifah Hanum; Affan Naufal; Susan M Sawyer (PLoS ONE)
Background Overweight and obesity are growing public health concerns globally for which innovative prevention and care delivery efforts are required. We recently developed a web-based training program to improve the quality of health professionals' weight management counseling of adolescents in Indonesia. Having previously confirmed its acceptability, this study aimed to measure the effectiveness of the program through a randomized controlled trial. Methods We recruited 64 primary healthcare professionals from 17 provinces across Indonesia who were randomized to participate in a 4-week online training program (intervention group [IG, n = 32] or a waitlist control group [CG, n = 32]). Using active learning approaches, the training program focused on adolescent development, psychosocial assessment, motivational interviewing (MI), and parent engagement. Participants in each arm were asked to record two counseling sessions with adolescents. These were objectively rated by trained psychologists using a validated tool, and also by qualitative assessment of counseling quality. In both groups, the first recorded counseling session occurred before the training. The second recording took place after the training for IG participants, but not for CG participants. Results IG participants demonstrated significant improvements in their knowledge and counseling skills (p<0.001, t-test). This included improvements in introductory remarks, quality of psychosocial assessment, and MI skills. There was no change in the extent of parental involvement. The MI training successfully oriented the counseling sessions towards a more collaborative and participatory conversation for supporting behavioral change. Conclusion This novel online training program improved the knowledge and counseling skills of Indonesian primary healthcare professionals. Greater emphasis on engaging parents and more guidance on conducting telehealth counseling may improve parental involvement in future iterations.